Penentuan Parameter Produksi Material Rem Ramah Lingkungan Untuk Aplikasi Kereta Api Menggunakan Serat Tandan Kosong Kelapa Sawit Sebagai Penguat - Hilman Syaeful A; IGN Wiratmaja Pudja; Agus Triono (Department of Mechanical Engineering, University of Udayana, 2012)
Evaluation to determine production parameters of material for train brake that is environmentally friendlyby using serat tandan kosong kelapa sawit (TKKS) as reinforcement was done by using extensionevaluation method. The research was carried out with variations some of parameter productions or bymaking material such as pressure load, pressure time and temperatures. The samples then were testedbased on criteria from the technical specification for composite brake from PT KAI. It is obtained fromthe testing that the best parameter productions are: Pressure 15 ton, pressuring time 40 minutes, andtemperature is 200oC. The result from evaluation indicate that sample S14 as the the best sample thatapproach technical spesification from the PT. KAI